Fish Oil-Derived Furan Fatty Acid: A New Player in the Regulation of Metabolic Syndrome and Fatty Liver Disease. (7th June 2021) - Rowart, Pascal; Salvatore, Sonia; Chang, Fei; Khoo, Nicholas; Schopfer, Francisco
Abstract: Objectives: Obesity and non-alcoholic fatty liver diseases (NAFLD) are multifactorial diseases that affect more than 35% of the world's population. Fish oil (FO) is an important dietary component that provides essential omega-3 fatty acids (Ω-3) effective for hypertriglyceridemia with eicosapentaenoic acid shown to reduce cardiovascular and metabolic syndrome-related events. However, the mechanisms involved in these beneficial activities are still unclear. A metabolomic study of healthy volunteers receiving Lovaza, an omega-3-drug, showed a large increase in plasma and urinary metabolite 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF). Moreover, in the diet-induced obesity (DIO) mouse model, CMPF was protective and reversed steatosis. We identified furan fatty acids (FuFA) present both in FO and Lovaza (0.1–1%) as the sources of CMPF and hypothesised that they were responsible for these beneficial effects. Methods: We synthesized one FuFA and confirmed its structure by NMR and mass spectrometry and tested whether it had protective effects in this DIO model (23 weeks, 60 kcal% fat). After 16 weeks of the diet, FuFA (25mg/kg/day) was administered by gavage for the last 7 weeks. A glucose tolerance test was performed at week 4 th . Tissues and blood were collected at week 7 th after 5h fasting. Mass spectrometry, ELISA, and multiplex analysis were performed on plasma. Liver staining (H&E) was also performed to quantify steatosis and ballooning. Results: The glucose tolerance test showed improved glucose clearance in FuFA-treated mice compared to vehicle. The fasting level of insulin and c-peptide 2 were respectively 2.9- and 1.5-fold lower in FuFA- compared to the vehicle-treated mice. Additionally, circulating TNF-α was significantly lower (1.6-fold) in FuFA-treated mice. NAFLD activity scores - hepatocytes ballooning and steatosis - were also significantly decreased in FuFA-treated mice by 1.6- and 1.4-fold, respectively. Finally, an MS-based analysis of plasma showed a significant decrease in cholesterol (1.2-fold) and cholesterol-ester (1.4-fold) levels in FuFA-treated mice. Conclusions: In conclusion, the beneficial effects observed in Ω-3 and FO treatment on DIO and NAFLD may be related to the presence of FuFA in these dietary preparations. Funding Sources: NIH.